“They just don't invest in those students…" Adult literacy education and the shift to career readiness: Conversations with veteran educators in the US - Jaye Jones (Adult Education Research Conference, 2020)
The 2014 reauthorization of the Workforce Innovation and Opportunity Act (WIOA) – a major source of funding for adult education programs in the United States – meant even greater emphasis on workforce-focused skills in the classroom and intensified tracking of occupational outcomes. Concerns have been raised about how a move away from critical literacy has impacted some of the field’s most vulnerable learners, those at the lowest levels of literacy. This paper examines the experiences of veteran adult literacy educators to illuminate the impact workforce-focused policies have had on educational services for adult literacy level learners.
Keywords: adult basic education; adult education policy; workforce development; WIOA